The Influence Of Brand Experience On Brand Loyalty In The Tiktok Shop Mobile Application With Brand Trust As a Mediating Variable - Gaka Awangga; Dorothy Rouly Haratua Pandjaitan (International Journal of Economics, Business and Innovation Research, 2026)
This study is motivated by the increasing competition in the social commerce industry and the shift in consumer behavior that emphasizes experiential aspects in online shopping. TikTok Shop, as one of the rapidly growing social media–based e commerce platforms in Indonesia, faces challenges in maintaining user trust and loyalty amid intense market competition. The purpose of this study is to examine the effect of Brand experience on Brand loyalty with Brand trust as a mediating variable. This research employs a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis technique with SmartPLS 4.0 software. Data were collected from 202 active TikTok Shop users selected through a purposive sampling technique. The results indicate that Brand experience has a positive and significant effect on both Brand trust and Brand loyalty. Brand trust also has a positive and significant effect on Brand loyalty and partially mediates the relationship between Brand experience and Brand loyalty. These findings demonstrate that positive experiences perceived by TikTok Shop users can enhance their trust in the platform, ultimately strengthening their loyalty. Therefore, TikTok Shop is advised to continuously improve the quality of user experience through sensory, affective, intellectual, and behavioral aspects to reinforce trust and build long-term customer loyalty.